AN INSTITUTIONAL AND NETWORK PERSPECTIVE OF ORGANISATIONAL LEGITIMACY: EMPIRICAL EVIDENCE FROM CHINA'S TELECOMMUNICATIONS MARKET - Brian Low, (Asian Academy of Management Journal, 2010)
This perspective paper combines institutional and industrial network theory to develop a framework for analysing organisational legitimacy. The main subject, Nokia China, is found to be sensitive to network-legitimating initiatives, with consequences that accommodate multiple, conflicting stakeholders? interests in China?s politically sensitive and protective telecommunications market. This paper offers new insights into institutional isomorphism that is manifested empirically as incremental conformity to regulative processes, institutional norms and cognitive knowledge and meanings within the environment, thereby extending commonly held views of institutional theory to include organisational legitimacy in industrial networks.